PENDIDIKAN MENURUT FILSAFAT IBNU SINA (980 M-1037 M) - Iskandar Yusuf; Khojir Khojir (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Ibn Sina is one of the Muslim philosophers who lived in the classical period of Islamic civilization who mastered various disciplines, especially in the medical and medical fields so that philosophical thought regarding education was in contact with Greek psychology and philosophy. Therefore, this article intends to explore information by departing from Ibn Sina's background as a person, the works produced and the results of thoughts about Islamic education in terms of scientific and human aspects, curriculum, educational goals, educators and students, methods to punishment. in education.